The use of the ASET in the diagnosis of ventriculoatrial shunt infection: a case report - Reaper, Jacqueline; Collins, Sally Ann; Bayston, Roger (BMJ Group, 2012)
A 38yr-old male with a ventriculoatrial shunt presented with nonspecific symptoms (headache, back pain, night sweats) and inconclusive laboratory results. He showed an extremely high titre of antibody to Staphylococcus epidermidis which proved diagnostic of shunt infection. This was confirmed on shunt removal and he was successfully treated.